Odpowiedzi

2009-11-16T18:27:00+01:00
2x² -3² = (x²-3)-(x+3)²=
2x² -9 = x² -3 - (x²+6x+9)=
2x² -9 = x² -3 -x² -6x -9 =
2x² -x² -x² +6x = -9 +9
6x = 0/:6
x = 0
2 3 2
2009-11-16T18:29:31+01:00
2x² -3² = (x²-3)-(x+3)²
2x² - 9 = (x²-3)-(x²+9)
2x² - 9 = x² - 3 - x² - 9
2x² - 9 = -12
2x² = -3 /:2
x² = - 1,5
x = √-1,5
2 3 2
2009-11-16T18:48:37+01:00
2x² - 3² = (x² - 3) - (x + 3)²
2x² - 9 = x² - 3 - x² - 6x- 9
2x - x² + x² + 6x - 9 + 3 + 9 = 0
2x² + 6x + 3 = 0
Δ = 6² - 4*3*2 = 12
√Δ = √12 = 2√3

x = ( -6 - 2√3 ) / 4 ∨ x = ( -6 + 2√3 ) / 4
x = (-3 - √3) / 2 ∨ x = (-3 + √3) / 2